The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1164/rccm.200701-051oc
|View full text |Cite
|
Sign up to set email alerts
|

Brief, Large Tidal Volume Ventilation Initiates Lung Injury and a Systemic Response in Fetal Sheep

Abstract: Ventilation for 15 minutes with a Vt of 15 ml/kg initiates an injurious process in the preterm lung and a hepatic acute-phase response. Subsequent ventilatory support causes further increases in some injury indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
229
2
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(243 citation statements)
references
References 55 publications
10
229
2
2
Order By: Relevance
“…It is well established that five large rapid inflations (> 8 ml/kg) at birth are sufficient to cause lung injury (49) and to initiate a systemic inflammatory cascade in the neonate (50). The bag-and-mask or T-piece circuits commonly used for neonatal resuscitation provide no feedback information on the V T being delivered.…”
Section: Inflammatory Consequences Of the Initiation Of Respiratory Smentioning
confidence: 99%
“…It is well established that five large rapid inflations (> 8 ml/kg) at birth are sufficient to cause lung injury (49) and to initiate a systemic inflammatory cascade in the neonate (50). The bag-and-mask or T-piece circuits commonly used for neonatal resuscitation provide no feedback information on the V T being delivered.…”
Section: Inflammatory Consequences Of the Initiation Of Respiratory Smentioning
confidence: 99%
“…It has been shown, for example, that even a brief MV with low V T induces TLR2 and TLR4 gene expression in previously healthy animals, together with mild lung inflammation [13,14]. It has also been reported that the genetic absence of TLR4 in mice decreases lung injury and especially PMN recruitment in a similar ''twohit'' model (high V T MV plus LPS challenge) [15].…”
mentioning
confidence: 99%
“…This reflects more effective airway liquid clearance, resulting in larger lung gas volumes. Although the PIPs required during the initial 40 inflations were higher than those routinely used in human infants, they are not dissimilar to those used in preterm lambs (31). Similarly, previous studies have investigated the effects of PEEP on pulmonary function in preterm lambs and found that lambs ventilated at high PEEP (12 cmH 2 O) initially had better lung function but all developed pneumothoraces and died within 90 min (35).…”
Section: Pips and Dynamic Pulmonary Compliancementioning
confidence: 87%
“…On the basis of our observations, this would be expected to facilitate FRC recruitment. Although large V T s facilitate FRC recruitment, they are largely thought to be injurious to the lung in newborn infants receiving respiratory support (31,32). Indeed, only six inflations of 35-40 ml/kg were sufficient to impair the response to surfactant and induce histological evidence of lung injury (3).…”
Section: Tmentioning
confidence: 99%